(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
Luis de Onís was a “pre-liberal” diplomat, who developed diplomatic activities for forty years both in Europe and America between the Ancien Regime and the liberal Triennium, known above all for the 1819 Treaty with the United States. He is an example of the adaptation of the elites in the transition to the contemporary age. From sources deposited in the National Historical Archive and the General Archive of the Indies, it was analyzed its vision of Ibero-America and the means proposed to contain its emancipation, highlighting its proposals of a more radical and realistic character with respect to the generality of the Spanish political class.